Design and Development of Arduino Mega-Based Vehicle Dimension Measurement Tool - Riz Rifai O. Sause; Adrian Pradana; Asep Eka Nugraha; Aris Budi Sulistyo; Rahmat Ahmad (Jurnal Teknologi Transportasi dan Logistik, 2022)
The measurement of the dimensions of a motorized vehicle is sometimes not carried out correctly and according to the measurement procedure which results in a size difference between the sizes listed on the Type Test Registration Certificate (SRUT) and the results of measurements in the field. The difference in size can result in the vehicle exceeding the specified dimensions or commonly referred to as over dimension and over loading (ODOL) conditions. The over- dimensional and over-loading (ODOL) vehicles will result in state losses in the form of road repair costs due to over-loading violations and/or over-size violations and result in an increase in the potential for traffic accidents due to over-dimensional and over-loading. One of the causes of errors in the process of measuring the dimensions of motorized vehicles is the process of measuring dimensions which are still done manually by motorized vehicle testers using a roll meter. These manual measurements are sometimes not carried out exactly at the measuring point and according to the size point of view so that the measurement results will be different from what they should be.